How Liberal is the Theory of Internacional Relations Rawls? - Loewe, Daniel (Veritas (Porto Alegre), 2015)
This paper contends that Rawls’s extension of his conception of domestic justice to the context of international relations is to be opposed to central premises of his own theory of justice. Consistent with his premises, any extension of Rawls’s theory of justice must recognize further demands, such as human rights, and it must accept a sort of global principle for distribution.